Does global drug innovation correspond to burden of disease? The neglected diseases in developed and developing countries. (12th November 2018) - Barrenho, Eliana; Miraldo, Marisa; Smith, Peter C.
Abstract: Although it is commonly argued that there is a mismatch between drug innovation and disease burden, there is little evidence on the magnitude and direction of such disparities. In this paper, we measure inequality in innovation, by comparing research and development activity with population health and gross domestic product data across 493 therapeutic indications to globally measure: (a) drug innovation, (b) disease burden, and (c) market size. We use concentration curves and indices to assess inequality at two levels: (a) broad disease groups and (b) disease subcategories for both 1990 and 2010. For some top burden disease subcategories (i.e., cardiovascular and circulatory diseases, neoplasms, and musculoskeletal disorders ), innovation is disproportionately concentrated in diseases with high disease burden and large market size, whereas for others (i.e., mental and behavioral disorders, neonatal disorders, and neglected tropical diseases ) innovation is disproportionately concentrated in low burden diseases. These inequalities persisted over time, suggesting inertia in pharmaceutical research and development in tackling the global health challenges. Our results confirm quantitatively assertions about the mismatch between disease burden and pharmaceutical innovation in both developed and developing countries and highlight the disease areas for which morbidity and mortality remain unaddressed.